Predictors for choosing the specialty of Family Medicine from undergraduate knowledge and attitudes - Ayuso-Raya, María Candelaria; Escobar-Rabadán, Francisco; López-Torres-Hidalgo, Jesús; Montoya-Fernández, Julio; Téllez-Lapeira, Juan Manuel; Campa-Valera, Francisco (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: A cold climate towards primary care (PC) within medical academia could form a barrier against choosing family medicine (FM) as a career option. This study was designed to determine whether medical students’ knowledge of and attitudes towards FM predicted their career choice. DESIGN AND SETTING: Cohort study conducted at two different medical schools. METHODS: After completing a PC course at the Albacete Medical School in 2005-2006, 81 second-year students were asked to give responses to a questionnaire. In their sixth year (2009-2010), 79 students in Albacete and 42 in Seville (taken as an unexposed cohort) were asked to give responses too. Their choice of specialty was investigated in 2011. RESULTS: In Albacete, the questionnaire was answered by 79 second-year and 76 sixth-year students; in Seville, it was answered by 26 sixth-year students. After completing the PC course, 69.3% said they would like to become a family doctor. This percentage decreased to 40.3% at the end of the undergraduate course (P < 0.0001). In the sixth year, the attitudes towards FM worsened, yet these were significantly more favorable than those in Seville. Only 12 students chose FM; they obtained significantly worse scores in their specialty selection examination than their peers (P < 0.0001). CONCLUSION: In the Albacete Medical School, the students’ opinion about FM worsened over the undergraduate course, although it was still better than the Seville students’ stance. In any case, FM was seen to be a minority option.